1995
DOI: 10.1016/0092-8674(95)90268-6
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fusion and the cell cycle: Cdc48p participates in the fusion of ER membranes

Abstract: The fusion of endoplasmic reticulum (ER) membranes in yeast is an essential process required for normal progression of the nuclear cell cycle, karyogamy, and the maintenance of an intact organellar compartment. We showed previously that this process requires a novel fusion machinery distinct from the classic membrane docking/fusion machinery containing Sec17p (alpha-SNAP) and Sec18p (NSF). Here we show that Cdc48p, a cell-cycle protein with homology to Sec18p, is required in ER fusion. A temperature-sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
291
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(303 citation statements)
references
References 31 publications
7
291
0
2
Order By: Relevance
“…However, it has been recently reported that ERresident mannosidase I is regulated by proteolysis mediated by the lysosomal compartment [52]. Since VCP is required for homotypic vesicle fusion in the ER and Golgi [53,54], VCP depletion likely diminishes the traffic of ER proteins to lysosomes providing an alternative explanation to increased levels of demannosylation of N-glycans in the absence of any direct effect of VCP on ERAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been recently reported that ERresident mannosidase I is regulated by proteolysis mediated by the lysosomal compartment [52]. Since VCP is required for homotypic vesicle fusion in the ER and Golgi [53,54], VCP depletion likely diminishes the traffic of ER proteins to lysosomes providing an alternative explanation to increased levels of demannosylation of N-glycans in the absence of any direct effect of VCP on ERAD.…”
Section: Discussionmentioning
confidence: 99%
“…Those changes may either reflect the different abundance of coreglycosylated precursors trafficked from the ER or -alternatively -they may indicate that VCP controls different aspects of glycosylation, for example the regulated degradation of glycosylation enzymes within a lysosomal compartment [52]. The latter possibility is supported by the fact that VCP is the major ATP-ase associated with transitional ER and the Golgi involved in homotypic membrane fusion within that compartment [53,54]. Depletion of VCP by RNAi may therefore affect the distribution of different glycosylation enzymes within cis, medial and trans cisternae of the Golgi apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…PAS is another member of the subfamily involved in membrane fusion events, whose mutant is incapable of forming peroxisomes from smaller precursors . Recently, two other kinds of membrane fusion events, ER fusion and Golgi cisternae formation, have been associated with AAA-proteins CDC48 (Latterich et al, 1995) and p97ATP-ase (Rabouille et al, 1995;Acharya et al, 1995), respectively. To date, however, none of the members in this subfamily have been associated with the membrane fusion events of mitochondria, one of the most abundant membrane-containing cellular organelles.…”
Section: Discussionmentioning
confidence: 99%
“…Using a biochemical assay, Latterich et al [12] first showed that S. cerevisiae Cdc48, an AAA ATPase with homology to the well-characterized fusion protein N-ethylmaleimide sensitive factor (NSF or Sec18), is required for ER-derived vesicle fusion. At the same time, the mammalian orthologue of Cdc48, p97, was shown to be involved in the reconstitution of Golgi cisternae from mitotic Golgi fragments [13].…”
Section: Homotypic Fusionmentioning
confidence: 99%